2012
DOI: 10.1128/jvi.02236-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Novel Reassortant H11N2 Avian Influenza Virus Isolated from a Live Poultry Market in Eastern China

Abstract: A/chicken/Nanjing/908/2009(H11N2) (CK908) was isolated from a live poultry market in Nanjing, China. Using PCR and sequencing analysis, we obtained the complete genome sequences of the CK908 virus. The sequence analysis demonstrated that this H11N2 virus was a novel reassortant AIV whose PB1, PB2, PA, HA, NP, NA, M, and NS genes originated from H9N2, H7N7, H5N2, H11N8, H3N6, H6N2, H1N1, and H5N1, respectively. Knowledge regarding the complete genome sequences of the CK908 virus will be useful for epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Although the H11 subtype has been found globally in wild birds, 13,16,44 few studies have identified H11 viruses from domestic poultry. 10,18,19 During active surveillance in a LAM in Colombia, we isolated H11 viruses from two separate birds. Phylogenic and sequence analysis of all gene segments showed their similarity to wild bird viruses of North American origin, similar to other H11 viruses obtained in Central and South America to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the H11 subtype has been found globally in wild birds, 13,16,44 few studies have identified H11 viruses from domestic poultry. 10,18,19 During active surveillance in a LAM in Colombia, we isolated H11 viruses from two separate birds. Phylogenic and sequence analysis of all gene segments showed their similarity to wild bird viruses of North American origin, similar to other H11 viruses obtained in Central and South America to date.…”
Section: Discussionmentioning
confidence: 99%
“…No changes associated with antiviral resistance were found. 42,43 Colombian H11N2 transmits in chickens Given that H11 infection in poultry is uncommon, 10,18,19 we evaluated the pathogenicity and transmissibility of a panel of related H11 viruses in chickens. The Colombian H11N2 viruses are virtually identical; thus, only A/Helmeted guineafowl/Colombia/2/2015 (HGF/Colombia) was used.…”
Section: Phylogenetic and Antigenic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…H11 subtype influenza viruses usually exist in birds belonging to the order Galliformes and include nine NA combinations. The N2, N3, and N9 subtype recombinants are capable of infecting ducks and have widely circulated in live poultry markets in China (Chen et al., ; Lam et al., ); however, these subtypes can also infect humans who are in frequent contact with infected birds (Gill, Webby, Gilchrist, & Gray, ; Zhang et al., ). Although H11 viruses have not been directly isolated from humans and have been observed to infect humans only through serological evidence, these viruses have shown combined two‐receptor specificity, that is, avian and mammalian (Gambaryan et al., ), which suggests that this subtype has the potential to cross the species barrier, infect mammals (Gambaryan et al., ), and threaten human health.…”
Section: Introductionmentioning
confidence: 99%
“…H11 subtype influenza viruses usually exist in birds belonging to the order Galliformes and include nine NA combinations. The N2, N3, and N9 subtype recombinants are capable of infecting ducks and have widely circulated in live poultry markets in China (Chen et al, 2012;Lam et al, 2013); however, these subtypes can also infect humans who are in frequent contact with infected birds (Gill, Webby, Gilchrist, & Gray, 2006;Zhang et al, 2012). Although H11 viruses have not been directly isolated from humans and have been *These authors are co-corresponding authors.…”
Section: Introductionmentioning
confidence: 99%